LED-Based Visible Light Communications - Chi, Nan (Signals and Communication Technology, 2018)
The book systematically introduces the visible light communication (VLC) technology in detail. Basic concepts and how to realize the system are both illustrated, including the transmitter, channel, and the receiver. In addition, a good many experimental results are presented to help readers further understand the VLC technologies. The upper-layer protocols of visible light communication system and the technology trends are also discussed. This book can be a good reference work for researchers, engineers, and graduate students in the fields of communications, LED, and optics.